Matematika Dalam Analisis Korupsi di Kota Medan Tahun 2023 serta Penanggulangannya - Sri Rizky Br Harahap; Gusti Arya Wicaksana; qwa Futri Anggraini; Sri Ulfa Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Mathematics always has an important meaning in life, everything in this world is inseparable from the name mathematics, therefore mathematics is also known as the Teacher of Life. With mathematics, all matters of life can be arranged systematically. What's more, besides managing the affairs of life, mathematics is also a reference in managing the future. The knowledge commonly used in mathematics is forecasting (Forecasting). Forecasting in mathematics is used to analyze conditions that may occur in the future, both in the near and long term. One of the applications of the mathematical method with the forecasting method that can be made is an analysis of the level of corruption in Medan City in 2023. This analysis is made as a reference for related parties so that they can socialize about the laws that apply to criminal acts of corruption in order to realize release to the public. The method used in the analysis of corruption figures in Medan City for 2023-2024 is a quantitative method using a mathematical model, namely Double Exponential Smoothing. The results of the analysis obtained are that the corruption rate in Medan City in 2023-2024 has decreased. However, this figure may not be achieved if corruption is not prevented in a certain way. Keywords: Forecasting, Mathematical Methods, Corruption, Community Service